Fires increase Amazon forest productivity through increases in diffuse radiation. Issue 11 (9th June 2015) - Rap, A.; Spracklen, D. V.; Mercado, L.; Reddington, C. L.; Haywood, J. M.; Ellis, R. J.; Phillips, O. L.; Artaxo, P.; Bonal, D.; Restrepo Coupe, N.; Butt, N.
Abstract Atmospheric aerosol scatters solar radiation increasing the fraction of diffuse radiation and the efficiency of photosynthesis. We quantify the impacts of biomass burning aerosol (BBA) on diffuse radiation and plant photosynthesis across Amazonia during 1998–2007. Evaluation against observed aerosol optical depth allows us to provide lower and upper BBA emissions estimates. BBA increases Amazon basin annual mean diffuse radiation by 3.4–6.8% and net primary production (NPP) by 1.4–2.8%, with quoted ranges driven by uncertainty in BBA emissions. The enhancement of Amazon basin NPP by 78–156 Tg C a−1 is equivalent to 33–65% of the annual regional carbon emissions from biomass burning. This NPP increase occurs during the dry season and acts to counteract some of the observed effect of drought on tropical production. We estimate that 30–60 Tg C a−1 of this NPP enhancement is within woody tissue, accounting for 8–16% of the observed carbon sink across mature Amazonian forests.